Effects of Heat Treatment on Microstructures and Corrosion Properties of AlxCrFeNi Medium-Entropy Alloy - Pushan Guo; Yuan Pang; Qingke Zhang; Lijing Yang; Zhenlun Song; Yi Zhang (Metals)
This study designed AlxCrFeNi (x = 0.8, 1.0, 1.2) medium-entropy alloys featuring a BCC + B2 dual-phase structure to systematically investigate the effects of Al content variation and heat treatment on microstructure evolution and corrosion behavior. Microstructural characterization revealed that all investigated alloys maintained the BCC + B2 dual-phase labyrinth structure. Electrochemical tests showed that as the Al content increased, the corrosion current density and corrosion rate in a 3.5 wt% NaCl solution increased. Synergistic analysis of post-corrosion morphology (through electrochemical testing and in-situ immersion) combined with XPS analysis of the passive films revealed that the initial stage of corrosion was primarily pitting. Subsequently, due to the loose and porous Al2O3 passive layer formed by the NiAl-rich phase, which was easily attacked by Cl− ions, the corrosion progressed into selective corrosion of the NiAl phase. Notably, heat treatment at 1000 °C induced microstructural refinement with enhanced coupling between chunky and labyrinth structures, resulting in improved corrosion resistance despite a 4–6% reduction in Vickers hardness due to elemental homogenization. Among the investigated alloys, the heat-treated Al0.8CrFeNi exhibited the most promising corrosion resistance.